Work-related factors affecting the retention of medical officers in the preventive health sector in Sri Lanka - Mahendra Arnold; Dinusha Fernando; Kapila Wickramanayake; Palitha Karunapema; Sepali Wickramatilake; Yamuna Fernando; Chandani Denawaka; Pasyodun Koralage Buddhika Mahesh; Sujeewa Pandithrathna (BMC, 2022)
Abstract Background Retention of human resources in the healthcare system, particularly doctors at district level is a great challenge faced by the decentralized health systems in poorly resourced countries. Medical Officers of Health (MOH), medical doctors who provide preventive health services, are a particularly important human resource in the preventive health sector in Sri Lanka. This study explores the relative importance of different factors affecting the retention of MOHs in the preventive health sector of Sri Lanka. Methods A descriptive cross-sectional study was carried out among Medical Officers of Health in the Colombo district with 18 MOH Offices with 74 medical officers. A pre-tested self-administered questionnaire was used as the study instrument. Data were analyzed using descriptive statistics, correlation and regression analyses. Results Of the 74 medical officers 64 responded with a response rate of response rate of 86.5%. Regression analysis showed that all four variables; recognition, work schedule, remuneration and responsibility are positively and significantly correlated with retention of Medical Officers of Health in the preventive health sector. The variable 'work schedule' showed the highest impact on the retention of Medical Officers of Health. Conclusions In order to retain trained Medical Officers of Health in the Sri Lankan preventive health sector, health authorities should address the factors identified in this study. If policymakers fail to address these factors, preventive health services will face negative implications due to the shortage of key service providers.